2020
DOI: 10.2298/tsci191115471u
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different fuel supply types on combustion characteristics behind group of V-gutter flame holders: Experimental and numerical study

Abstract: Experiments on fuel effects flame stabilization processes, NOx generation and temperature at combustion chamber outlet when using a group of three V-gutter flame holders have been reported. Fuel supply directly to the re-circulation zone on the inside of the V-gutter (type A fuel supply), and alternatively in the second type, fuel was supplied to the V-gutter symmetry axis on the outside (type B fuel supply have been carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
4
0
2
Order By: Relevance
“…Previous studies of combustion processes have shown that the turbulence model has a sufficient level of accuracy [15,16], which determined the choice of this model. The injection model was used to model liquid fuel injection.…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of combustion processes have shown that the turbulence model has a sufficient level of accuracy [15,16], which determined the choice of this model. The injection model was used to model liquid fuel injection.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The importance of both the combustion efficiency and the environmental impact forms special demand on the combustion devices constructions [15,16]. Following this line, the present work addresses experimental and numerical studies of new combustion device with the premised fueloxidant flow.…”
Section: Introductionmentioning
confidence: 99%
“…The test results presented in this paper were obtained for a lean biogas/air mixture, and relate to flame front velocity, temperature profile, emission, and flame structure. [10,19] The flame structure and combustion emissions [17], with a laminar premixed flame, of a lean biogas/air mixture [14] at an initial temperature of 298 K and a pressure of 1.013 x 10 5 Pa were calculated. The calculation was performed in the domain of 10 cm, which is significantly more than the thickness of the flame.…”
Section: Flame Structure and Emissions In Premixed Biogas Flamesmentioning
confidence: 99%
“…An analysis of the main reasons for the formation of nitrogen oxides in various devices and the prospects for the development of the power industry showed that traditional methods of fuel combustion do not provide the required parameters. Improving the efficiency of fuel combustion can be obtained by using microflame combustion [1][2][3].…”
Section: Introductionmentioning
confidence: 99%